A proposal for self-listening: 3 movements for self-listening - Ferreira, Marina Mapurunga de Miranda (2024)
Writing can propose listening, just as listening can generate writing. I present a piece of writing that started from a self-listening and now I propose another listening for the reader. This proposal involves a self-listening that can be physiological, in search of the sounds of one's own body, as well as a psychological listening that wanders through drifting thoughts. This self-listening can also be focal and global. As much as we try to focus on a specific sound, our ear opens up to more open “frames”, whether these are internal or external to us. This listening practice can be done individually or in a group. In a group, each person's experience can be discussed and shared after the practice. What did I listen to that the other person also listened to? What did I listen that the other person didn't? How can I share my self-listening? Through new writing, a drawing, a draft?